ANALISIS MANAJEMEN RISIKO KREDIT PADA PT BANK NEGARA INDONESIA (PERSERO) TBK - Kartini, Ida Ayu Nuh; Djonien, Azarya B.; Aziz, M. Saiful; Ilham, M. Shafrial; Prasetya, Mahfud Eko (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This community service initiative seeks to improve the general public's understanding of credit risk management within the banking industry, an essential factor for ensuring financial stability and promoting sustainable economic growth. The program was designed to deepen participants' knowledge of credit risk management techniques, specifically examining PT Bank Negara Indonesia (Persero) Tbk. It covered aspects such as credit distribution and the significance of the Loan to Deposit Ratio (LDR). Employing descriptive and educational approaches, the activity utilized literature reviews, presentations, and discussions based on official banking reports and regulatory standards. Findings revealed that participants demonstrated enhanced awareness and understanding of key concepts such as responsible credit management, risk identification, mitigation strategies, and liquidity management in banking operations. This initiative plays a vital role in bolstering financial literacy and fostering the adoption of effective banking practices within the community, particularly among students and those interested in finance and banking careers.